Non-alcoholic fatty liver disease and metabolic syndrome in Brazilian middle-aged and older adults - Karnikowski, Mauro; Córdova, Cláudio; Oliveira, Ricardo Jaco de; Karnikowski, Margô Gomes de Oliveira; Nóbrega, Otávio de Tolêdo (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVES: Non-alcoholic fatty liver disease (NAFLD) is a complex clinicopathological entity characterized by diffuse or focal fat accumulation in the hepatic parenchyma of patients who deny abusive alcohol consumption. This study aimed to assess idiopathic NAFLD in community-dwelling, middle-aged and older adults living in the Brazilian Federal District. Associations between NAFLD and components of metabolic syndrome and the whole syndrome were investigated. DESIGN AND SETTINGS: This was a cross-sectional study on 139 subjects aged 55 years or older. METHODS: NAFLD was diagnosed by means of clinical procedures, to exclude subjects with signs of liver disorders, abusive alcohol consumption and infl uence from hepatotoxic drugs. Phenotypes were graded based on ultrasound examination. Metabolic syndrome was defi ned using the NCEP ATP III criteria. Laboratory tests were performed to assist clinical examinations and defi ne the syndrome. RESULTS: NAFLD was present in 35.2% of the subjects. Taken together, the two most intense phenotypes correlated with increased serum fasting glucose, triglyceride and VLDL cholesterol levels. Metabolic syndrome was diagnosed in 25.9% of the sample. In addition to associating NAFLD with specifi c traits of metabolic syndrome, non-parametric analysis confi rmed the existence of a relationship (p < 0.05) between the steatotic manifestation and the syndromic condition. CONCLUSION: Compared with the literature, this study reveals greater frequency of idiopathic NAFLD among Brazilian middle-aged and older adults than is described elsewhere. The fi ndings also suggest that impaired glycemic metabolism coupled with increased fat delivery and/or sustained endogenous biosynthesis is the most likely physiopathogenic mechanisms underlying the onset of NAFLD in this population.